The battle of the sexes / a Monja Danischewsky production ; written and produced by Monja Danischewsky ; directed by Charles Crichton. - Sellers, Peter, 1925-1980; Morley, Robert; Cummings, Constance, 1910-2005; Francis, Freddie, 1917-2007; Black, Stanley; Thurber, James, 1894-1961. (KL studio classics., 2016)
Shaking the very foundation of a men-only company, an accomplished business woman attempts to contemporize a manufacturing company.